Corporate Social Responsibility, Leverage, and Firm Size on Tax Aggressiveness in Indonesia - Sani, Cici Sabrina Kirani; Dewi, Anita Kusuma; Ridwansyah, Eksa (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the effects of corporate social responsibility, leverage, and firm size on tax aggressiveness in energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023. Methodology/approach: This study uses secondary financial report data with purposive sampling, yielding 88 observations. Tax aggressiveness is measured by Effective Tax Rate (ETR), with CSR and firm size as Dummy Variables and Leverage (DER) as an independent variable, analyzed using multiple linear regression in SPSS. Results/findings: The results show that Corporate Social Responsibility (CSR) has a positive but insignificant effect on tax aggressiveness; leverage has a positive and significant effect on tax aggressiveness; and firm size has a negative and significant effect on tax aggressiveness. Conclusions: The results show that tax aggressiveness in energy sector companies is more influenced by leverage and firm size than by CSR, where higher leverage increases tax aggressiveness, while larger firms tend to be less aggressive due to greater public scrutiny. Limitations: The research is limited to energy companies listed on the IDX during 2020–2023, so the findings may not be generalized to other sectors or periods Contributions: This study provides empirical evidence of tax aggressiveness in the energy sector and insights for investors, regulators, and management regarding the factors influencing corporate tax compliance.